Josip Široki, singer and transcriber at the same time - Tiefenthaler, Vera (Traditiones (Ljubljana), 2005)
The autor's aim was to discover what influence Josip Široki's activities have had on folk song collection. This is of special interest because he was working on a collection of folk songs at the same time that the Austrian program Austrian folk songs was being carried out. It is shown that Široki's methods differed significantly from the common methods applied at his time. Inaddition, light is shed on Široki's possible motivation to collect folk songs and how his work was influenced by other disciplins.
Keywords: Široki, Josip, 1882-1963; ethnology; etnologija; folkloristics; folkloristika; etnomuzikologija; hrvaške ljudske pesmi; Austria; Avstrija; zgodovinski pregledi